114 Decision making and consent: a junior doctor's perspective. (15th December 2021) - Billington, Jennifer; Varadkar, Sophia; Hardy, Charlie Meredith; Cross, Kate
Abstract : Background: Shared decision making and consent are fundamental to good medical practice. Since the introduction of The Montgomery Principle in 2005, there have been two further reforms in GMC Consent guidance. The most recent came into effect in November 2020 and focuses on seven principles of decision making and consent. Consent should be a meaningful, personalised dialogue between a doctor and their patient, with proportionate approach to risks for each situation. Methods: Since Junior doctors are major stakeholders in consent, the aim of this project was to capture their views on our current consent process after new guidance was issued. A short, free text questionnaire was sent to trust Junior doctors in June 2021 with the following questions(i)Department (ii)What does and does not work well with the current trust consent process. Questionnaire responses were coded to allow themes to emerge. Results: 68 Junior doctors responded, with representation from all departments. The majority of respondents feel well supported when obtaining consent and there is excellent access to consent forms. Doctors feel comfortable consenting for procedures within their speciality. The majority of doctors mentioned feeling uncomfortable when consenting for procedures outside their remit (e.g., line insertion, MRI). There is a clear desire to have electronic consent within the trust. Many doctors are concerned they will be unable to answer parents' questions for such procedures, and are unclear how to deal with such situations. It was a common theme that the consent process could be improved within the trust, particularly around complex patients under multiple specialties. Conclusion: This qualitative piece of work highlights a good support structure for Junior Doctors in our trust, and ongoing education and training would be beneficial. The current process of consent is not ideal for all situations. This work is part of an ongoing trust wide project which aims to ensure consent is in accordance with the latest GMC guidance to provide the best care for our patients.